β‐endorphin level and Lactate elimination: Effects on the shot and sprint performances in amateur soccer players - Vural, Faik; Turgay, Faruk; Balyan, Melih; Akşit, Tolga; Özkol, Mehmet Zeki (Progress in Nutrition, 2021)
Study Objectives: This study aimed to examine the effects of lactate elimination and saliva β‐endorphin (β-End) levels on the decrease in shot and sprint performances in the last period of a soccer match, and changes in saliva cortisol and testosterone levels during the match and their relationship to performance parameters. Methods: Twenty-two trained amateur soccer players performed the 90 minutes soccer match, while saliva β-End, testosterone, cortisol, blood lactate, and glucose measurements were obtained pre-match (M1), after 1st half (M2), and after the 2nd half (M3). Sprint and shot performances were assessed after warm-up and match play and after the Yo-Yo intermittent recovery test level 1 (Yo-Yo IR-1) test. Lactate elimination was evaluated with the Yo-Yo IR-1. Results: Soccer match-play elevated some individual β-End levels between M1 and M3 (an increase of %25) but overall differences between M1, M2, and M3 were not significant (%3.34 increase from M1 to M2, %1.12 increase from M1 to M3, and %2.17 decrease from M2 to M3). M3 testosterone levels significantly increased above basal (p < 0.01) and M2 levels (p < 0.001). Moreover, β-End levels and lactate elimination speeds were not significantly correlated with sprint and shot performance at M3 (p > 0.05). Conclusion: Our results suggest that β‐End and lactate elimination is not effective on the differences in shot and sprint performances after exercise. Therefore, future studies will appropriate for the examination of β‐End and other hormone levels to understand the exact mechanisms involved in different levels of soccer players.